2022
DOI: 10.1038/s41467-022-35629-z
|View full text |Cite
|
Sign up to set email alerts
|

Implantable niche with local immunosuppression for islet allotransplantation achieves type 1 diabetes reversal in rats

Abstract: Pancreatic islet transplantation efficacy for type 1 diabetes (T1D) management is limited by hypoxia-related graft attrition and need for systemic immunosuppression. To overcome these challenges, we developed the Neovascularized Implantable Cell Homing and Encapsulation (NICHE) device, which integrates direct vascularization for facile mass transfer and localized immunosuppressant delivery for islet rejection prophylaxis. Here, we investigated NICHE efficacy for allogeneic islet transplantation and long-term d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…The semiopen structure of laminates may be further developed to balance the immunoprotection and the nutrient supply to ensure the long-term efficacy of encapsulated islets. On the one hand, host tissues, especially vascular tissues, connected with the circulatory system of the body should be integrated in the devices to sustain the engraftment of the islets. , Prevascularization at the implant sites would be a favorable and practical solution to this problem. , Besides, as the concept of local immunomodulation or immunosuppression has drawn growing attention in β-cell therapy, design of incorporation of functional cells or drugs that could mitigate the immune clearance against β cells in the devices would probably further improve the success of cell therapy in T1D. To this end, when drugs or cells with local immune-suppression function are incorporated and the implant site is prevascularized, the laminate with cell-penetrable edges and gaps in the semiopen structure may favor the in-growth of vascular tissues, which would benefit the long-term engraftment of the islets.…”
Section: Discussionmentioning
confidence: 99%
“…The semiopen structure of laminates may be further developed to balance the immunoprotection and the nutrient supply to ensure the long-term efficacy of encapsulated islets. On the one hand, host tissues, especially vascular tissues, connected with the circulatory system of the body should be integrated in the devices to sustain the engraftment of the islets. , Prevascularization at the implant sites would be a favorable and practical solution to this problem. , Besides, as the concept of local immunomodulation or immunosuppression has drawn growing attention in β-cell therapy, design of incorporation of functional cells or drugs that could mitigate the immune clearance against β cells in the devices would probably further improve the success of cell therapy in T1D. To this end, when drugs or cells with local immune-suppression function are incorporated and the implant site is prevascularized, the laminate with cell-penetrable edges and gaps in the semiopen structure may favor the in-growth of vascular tissues, which would benefit the long-term engraftment of the islets.…”
Section: Discussionmentioning
confidence: 99%
“…A recent example is the neovascularized implantable cell homing and encapsulation (NICHE) device, which demonstrated long-term graft survival and diabetes reversal in allogenic subcutaneous transplants using rats and NHPs. [122] The device can be implanted before cell seeding to allow for prevascularization and provides an opportunity for direct subcutaneous injection of therapeutic drugs into the device for local immunomodulation, as demonstrated in the study with an immunosuppressive drug cocktail (CTLA4Ig and rabbit antilymphocyte serum for rats and anti-thymocyte globulin, CTLA4Ig, and anti-CD154 for NHPs). A comprehensive review regarding local immunomodulation for cell therapies can be found in the review article by Nash et al [123] and specifically in the context of islet transplantation in the article by Wang et al [28b] The co-encapsulation of support cells for improved islet function is another innovative approach to improve some of the shortcomings associated with macroencapsulation devices, particularly the issues with lack of vascularization and fibrosis/immune cell infiltration.…”
Section: Bmx-001mentioning
confidence: 99%
“…Also, they verified PA's suitability as a material for NICHE construction, integration, and vascularization. [ 88 ]…”
Section: Use Of Immunomodulatory Biomaterials In Various Biomedical A...mentioning
confidence: 99%